(untitled) (Research, Society and Development, 2021)
The aim of the study was to evaluate the effect of the essential oils of Origanum vulgare L. (EOO) and carvacrol (CAR) without growth from bacteria oropharynx. The microbiological techniques were applied: agar diffusion method, minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The ANOVA test was applied, with the Tukey test. The level of significance adopted was 5%. Tested strains were Pseudomonas aeruginosa ATCC 27853, Staphylococcus aureus ATCC 15656, Escherichia coli ATCC 25922 and Klebsiella pneumoniae INCQS 00147. The EOO showed antimicrobial activity, varying the size of the halos from 21.00 (± 0.20) mm, for E. coli, to 33.56 (± 14.32) mm, for S. aureus. The CAR has MIC lower for K. pneumoniae and a higher concentration for S. aureus. The MBC showed similar values the MIC. Origanum vulgare L. essential oil and carvacrol showed an inhibitory effect on the growth of bacteria in the oropharynx.